PROSES PERUMUSAN KEBIJAKAN PENDIDIKAN ISLAM DI MADRASAH PAB HELVETIA: STUDI ANALISIS KEBIJAKAN PUBLIK - Darmansah, Tengku; Maulana, Fiky; Damanik, Wiliana; Sembiring, Dinda Salsabilah; Purba, Try Aisyah Rani (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2026)
This study aims to analyze the formulation process of Islamic education policies at Madrasah PAB Helvetia using a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis to examine the roles of actors, policy formulation stages, and challenges in policy implementation. The findings reveal that policy formulation is carried out through participatory problem identification, development of policy alternatives, hierarchical decision-making, and periodic evaluation. The principal plays a strategic role, Islamic Education (PAI) teachers serve as key sources of pedagogical information, and the school committee provides social legitimacy for policy decisions. Implementation of the policies faces several challenges, including limited resources, resistance to change, and the diverse abilities of students. The study concludes that Islamic education policy formulation is a dynamic process shaped by actor interactions as well as internal and external conditions of the madrasah. Strengthening policy governance, developing measurable evaluation indicators, and enhancing resource capacity are essential to improving the effectiveness of Islamic education policy in madrasas.